Epidemiology of Ulnar Collateral Ligament Reconstruction in Major and Minor League Baseball Pitchers: Comprehensive Report on 1, 313 Cases. Issue 7 (21st July 2017) - Camp, Christopher L.; Conte, Stan; D'Angelo, John; Fealy, Stephen
Objectives: Although much as been done to better understand and characterize the epidemic of UCL reconstruction in pitchers, a comprehensive review of all UCL reconstructions performed in professional baseball pitchers is surprisingly lacking. Accordingly, t he purpose of this work was to provide an epidemiologic report on every UCL reconstruction ever performed in professional baseball with a special focus on outcomes (return to play rates and time) and overall survivorship. Methods: Three resources (including the Major League Baseball [MLB] injury tracking system) were combined and cross-referenced to identify all professional baseball players who had ever undergone primary UCL reconstruction (1974 to 2015). Variables analyzed included the date of injury, date of surgery, time out of play, geographical region, and revision status. Trends over time were analyzed collectively and based on level of play at the time of surgery. A minimum of 2 years of follow up was required to determine return to play status. Revision free Kaplan-Meier survivor analysis was performed. Results: A total of 1, 313 UCL reconstructions were identified. The annual rate of primary and revision UCL reconstructions rose significantly for all levels of play from 1974 to 2015 and from (p<0.001). The overall mean time to return to play (RTP) was 436 days (range 98 to 1, 643). The rate of RTP to any level was 93.9% for MLB pitchers vs. 76.3% for MiLB pitchers (p<0.001), and MLB pitchers RTP at the MLB level in 73.1% of cases. The time to RTP was longer (by 54 days) for revisions (p=0.025) compared to primaries, and MLB pitchers RTP from primary surgery 95.6% of the time but only 81.8% for revision surgery (p=0.008). The revision rate was 10.7%, and the percentage of players free of revision and still playing professional baseball was 92% at 2 years, 53% at 5 years, and 17% at 10 years. Survivorship was improved for players undergoing UCL reconstruction before age 25 opposed to after 25. Conclusion: This study represents the most robust epidemiologic report of UCL reconstruction in baseball to date, and a number of novel findings are reported. A number of key differences in MLB and MiLB, as well as primary and revision surgeries, were identified. Although the revision rate (10.7%) is higher than prior reports, 75% of players who had surgery before age of 25 are revision free and still playing professional baseball four years post operative.